Power output and power coefficient calculations of a small HAWT with tubercles using Blade Element Momentum Theory. Issue 1 (March 2021) - Damirez, V; Augusto, G
Abstract: A 0.6 m diameter, three-bladed, untwisted, fixed-pitch, and small horizontal axis wind turbine with tubercles was analysed using the Blade Element Momentum (BEM) Theory. Calculation frameworks based from the Original BEM Theory, Wilson-Walker Method, Glauert's Empirical Formula, and Buhl's Theory were used in the prediction of the power output and power coefficient. Numerical results from the calculation frameworks were compared to the experimental data taken from the literature. The power output predicted by the Buhl's Theory was the closest to the actual results. In the case of the power coefficient, the Wilson-Walker Method produced an almost equal prediction at λ=4.06, showing only a percentage difference of 0.47%. Results also showed that the power coefficient predicted by the four calculation frameworks were more accurate at higher tip speed ratios.